The Social Context Of Hadith History From The Perspective Of Hadith Sociology - Wiwaha, Rizzaldy Satria; Hidayati, Alfi Nur; Hanifah, Siti Nur; Wicaksono, Muhammad Bagus; Lubis, Taufik Haris (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study aims to understand the role of social interaction in the history of hadith transmission and understanding in Islamic societies. This study is often called the sociology of hadith. The sociology of hadith involves the study of social relationships, social structures, and social dynamics that influence the collection, transmission, and interpretation of hadith. The research method used is a literature study approach by collecting and analyzing various relevant sources including books, articles, and related research. The research involved exploring the sociological aspects of the hadith tradition such as the social factors that influence the transmission of hadith, the role of social groups in the interpretation of hadith, and the social dynamics in the establishment of hadith authority. The results show that the sociology of hadith plays an important role in understanding the complex social relationships involved in the transmission and understanding of hadith. Factors such as social, cultural, political and economic contexts play a role in influencing the interpretation and reception of hadith by the people. In addition, social groups such as scholars, lay people and religious institutions also play a significant role in shaping the authority of the hadith and determining its influence in society. This study also reveals the importance of the sociological study of hadith in the context of social change and the development of modern society. Social change, globalization and the challenges of the times affect how hadith are understood, accepted and applied in daily life. Therefore, this study focused on how the sociology of hadith approach can provide valuable insights in facing these challenges. In conclusion, an understanding of the sociology of hadith is essential in understanding the social dynamics of the hadith tradition. This study contributes to broadening the academic horizon on the role of social interaction in the transmission and understanding of hadith as well as providing a more comprehensive understanding of the social complexities involved in the hadith tradition.